Vectors $\overrightarrow{A}$ and $\overrightarrow{B}$ are shown. What is the magnitude of a vector $\overrightarrow{C}$ if $\overrightarrow{C}=\overrightarrow{A}-\overrightarrow{B}$?
$\text{A}\text{. }40\sqrt{3}$
$\text{B}\text{. }40\sqrt{2}$
$\text{C}\text{. }40$
$\text{D}\text{. 2}0$
Answer
Verified
472.5k+ views
Hint: Draw the vector $\left( -\overrightarrow{B} \right)$ and find the angle between the vectors $\overrightarrow{A}$ and $\left( -\overrightarrow{B} \right)$. The magnitude of vector $\left( -\overrightarrow{B} \right)$ is equal to the magnitude of vector $\overrightarrow{B}$. However, both the vectors are opposite directions. Then use the formula for the magnitude of the resultant of two vectors.
Formula used: $R=\sqrt{{{A}^{2}}+{{B}^{2}}+2AB\cos \theta }$
Complete step by step answer:
The vectors $\overrightarrow{A}$ and $\overrightarrow{B}$ are given. We are asked to find the magnitude of the vector $\overrightarrow{C}=\overrightarrow{A}-\overrightarrow{B}$. This vector addition can also be written as $\overrightarrow{C}=\overrightarrow{A}+\left( -\overrightarrow{B} \right)$.
Let us first draw the vector $\left( -\overrightarrow{B} \right)$. Vector $\left( -\overrightarrow{B} \right)$ is a vector whose magnitude is equal to the magnitude of vector $\overrightarrow{B}$ but its direction is opposite to the direction of $\overrightarrow{B}$ (as shown).
From the figure we get to know that the angle between the vectors $\overrightarrow{A}$ and $\left( -\overrightarrow{B} \right)$ is ${{120}^{\circ }}$.
Let us know use the formula for the magnitude of the resultant of the two vectors, i.e. $R=\sqrt{{{A}^{2}}+{{B}^{2}}+2AB\cos \theta }$ ….. (i), where are R is the magnitude of the resultant, A and B are the magnitudes of the two vectors and $\theta $ is the angle between the two vectors.
In this case, R = C, A = 40.
The magnitude of $\left( -\overrightarrow{B} \right)$ is equal to the magnitude of $\overrightarrow{B}$. Therefore, B = 40.
And $\theta ={{120}^{\circ }}$.
Substitute the values in (i).
$\Rightarrow C=\sqrt{{{40}^{2}}+{{40}^{2}}+2(40)(40)\cos {{120}^{\circ }}}$.
The value of $\cos {{120}^{\circ }}=-\dfrac{1}{2}$.
$\Rightarrow C=\sqrt{{{40}^{2}}+{{40}^{2}}+2(40)(40)\left( -\dfrac{1}{2} \right)}=\sqrt{{{40}^{2}}+{{40}^{2}}-{{40}^{2}}}=\sqrt{{{40}^{2}}}=40$.
This means that the magnitude of $\overrightarrow{C}$ is 40.
So, the correct answer is “Option C”.
Note: Alternative solution:
The magnitude of resultant of $\overrightarrow{C}=\overrightarrow{A}-\overrightarrow{B}$, is given as $C=\sqrt{{{A}^{2}}+{{B}^{2}}-2AB\cos \theta }$ ….. (1), where $\theta $ is the angle between the two vectors $\overrightarrow{A}$ and $\overrightarrow{B}$.
Therefore, A = B = 40 and $\theta ={{60}^{\circ }}$.
Substitute the values in (1).
$\Rightarrow C=\sqrt{{{40}^{2}}+{{40}^{2}}-2(40)(40)\cos {{60}^{\circ }}}=\sqrt{{{40}^{2}}+{{40}^{2}}-2(40)(40)\left( \dfrac{1}{2} \right)}=\sqrt{{{40}^{2}}+{{40}^{2}}-{{40}^{2}}}=\sqrt{{{40}^{2}}}=40$.
Formula used: $R=\sqrt{{{A}^{2}}+{{B}^{2}}+2AB\cos \theta }$
Complete step by step answer:
The vectors $\overrightarrow{A}$ and $\overrightarrow{B}$ are given. We are asked to find the magnitude of the vector $\overrightarrow{C}=\overrightarrow{A}-\overrightarrow{B}$. This vector addition can also be written as $\overrightarrow{C}=\overrightarrow{A}+\left( -\overrightarrow{B} \right)$.
Let us first draw the vector $\left( -\overrightarrow{B} \right)$. Vector $\left( -\overrightarrow{B} \right)$ is a vector whose magnitude is equal to the magnitude of vector $\overrightarrow{B}$ but its direction is opposite to the direction of $\overrightarrow{B}$ (as shown).
From the figure we get to know that the angle between the vectors $\overrightarrow{A}$ and $\left( -\overrightarrow{B} \right)$ is ${{120}^{\circ }}$.
Let us know use the formula for the magnitude of the resultant of the two vectors, i.e. $R=\sqrt{{{A}^{2}}+{{B}^{2}}+2AB\cos \theta }$ ….. (i), where are R is the magnitude of the resultant, A and B are the magnitudes of the two vectors and $\theta $ is the angle between the two vectors.
In this case, R = C, A = 40.
The magnitude of $\left( -\overrightarrow{B} \right)$ is equal to the magnitude of $\overrightarrow{B}$. Therefore, B = 40.
And $\theta ={{120}^{\circ }}$.
Substitute the values in (i).
$\Rightarrow C=\sqrt{{{40}^{2}}+{{40}^{2}}+2(40)(40)\cos {{120}^{\circ }}}$.
The value of $\cos {{120}^{\circ }}=-\dfrac{1}{2}$.
$\Rightarrow C=\sqrt{{{40}^{2}}+{{40}^{2}}+2(40)(40)\left( -\dfrac{1}{2} \right)}=\sqrt{{{40}^{2}}+{{40}^{2}}-{{40}^{2}}}=\sqrt{{{40}^{2}}}=40$.
This means that the magnitude of $\overrightarrow{C}$ is 40.
So, the correct answer is “Option C”.
Note: Alternative solution:
The magnitude of resultant of $\overrightarrow{C}=\overrightarrow{A}-\overrightarrow{B}$, is given as $C=\sqrt{{{A}^{2}}+{{B}^{2}}-2AB\cos \theta }$ ….. (1), where $\theta $ is the angle between the two vectors $\overrightarrow{A}$ and $\overrightarrow{B}$.
Therefore, A = B = 40 and $\theta ={{60}^{\circ }}$.
Substitute the values in (1).
$\Rightarrow C=\sqrt{{{40}^{2}}+{{40}^{2}}-2(40)(40)\cos {{60}^{\circ }}}=\sqrt{{{40}^{2}}+{{40}^{2}}-2(40)(40)\left( \dfrac{1}{2} \right)}=\sqrt{{{40}^{2}}+{{40}^{2}}-{{40}^{2}}}=\sqrt{{{40}^{2}}}=40$.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE